Implantable cardioverter defibrillator (ICD) deactivation discussions: Reality versus recommendations. (February 2016) - Hill, Loreena; McIlfatrick, Sonja; Taylor, Brian J; Dixon, Lana; Cole, Ben R; Moser, Debra K; Fitzsimons, Donna
Background: The implantable cardioverter defibrillator (ICD) is a cornerstone in the treatment of life-threatening arrhythmias. As rates of device implantation continue to rise throughout Europe, European and International guidelines recommend professionals discuss deactivation with patients. In reality the appropriate therapeutic management of an ICD at the end-of-life remains uncertain in the minds of professionals and patients. Aim: To identify current practice and examine professional decision-making for patients with an ICD from time of implantation to final documentation and demise. Methods: Retrospective case note review of patients with an ICD who died during a 12 month period at a regional implantation centre. Results: Fifty-nine patients were identified and medical notes of 44 of these patients were successfully retrieved. The majority of patients were male, mean age at time of death 73 years with one-third diagnosed with a malignancy prior to death. There was no documented evidence patients were informed about deactivation prior to ICD implantation. End-of-life management was discussed with 23 patients and on 17 occasions deactivation was included. Median time from discussion to death was seven days. In total 62.5% of patients who experienced a shock had an active ICD at death, while 93.7% who had their ICD deactivated never had a shock ( p =0.003). Conclusion: Patients were not adequately informed regarding device deactivation prior to implantation, nor when their health deteriorated. The experience of a shock potentially affects professional decision making regarding device deactivation.